(untitled) (Contemporary Central & East European Law, 2020)
Domestic legislation and international instruments designed for the protection of human rights provide for general clauses allowing limitations of rights and freedoms, e.g. public morals. A preliminary analysis of the case-law leads to the observation that both national courts and the European Court of Human Rights, when dealing with cases concerning sensitive moral issues, introduce varied argumentation methods allowing them to avoid making direct moral judgments and relying on the legitimate aim of protecting morality. In the article the Authors analyse selected judicial rulings in which moral issues may have played an important role. The scrutiny is done in order to identify and briefly discuss some examples of ways of argumentation used in the area under discussion by domestic and international courts. The identification of the courts’ methods of reasoning enables us in turn to make a preliminary assessment of the real role that the morality plays in the interpretation of human rights standards. It also constitutes a starting point for further consideration of the impact of ideological and cultural connotations on moral judgments, and on the establishment of a common moral standard to be applied in cases in which restriction on human rights and freedoms are considered.